Acute coronary syndromes without persistent ST-segment elevation: advances in surgical revascularization - Zoffoli, G.; Nicolini, F.; Beghi, et al., C (Acta Biomedica Atenei Parmensis, 2005)
Coronary artery bypass grafting (CABG) still plays a fundamental role in the management of acute coronary syndromes. The aim of this study is to report the experience of our center in the treatment of patients with acute coronary sindromes without persistent ST elevation urgently operated on with CABG, and to discuss surgical problems related.Two-hundred and six patients were urgently operated on for CABG for acute coronary syndromes without persistent ST-segment elevation from January 2001 to February 2003. The majority of them had three vessel coronary disease (72%) and left main stem disease occurred in 20% of the patients. Mean LVEF (left ventricular ejection fraction) was 54±12% whereas 9% of the patients had a LVEF<40%. Twenty-one patients (10%) received glycoprotein IIb/IIIa receptor inhibitors and 35 (17%) received intravenous heparin therapy before surgery. Mean interval time between the onset of symptoms and surgery was 16±10 days (range 4-50). In-hospital mortality was 2% (4 patients). Perioperative AMI (acute myocardial infarction) occurred in 4% (8 patients) and a transient low cardiac output syndrome in 27 patients (13%). Bleeding requiring surgery occurred in 1% of the patients.Transient respiratory insufficiency was present in 12 patients (6%) and acute renal failure in 8 patients (4%). Mean I.C.U. time was 2.4 days (1-17). Urgent CABG for acute coronary syndromes shows a low risk for in-hospital mortality and morbidity. In acute patients arterial grafts are not detrimental for the outcome, but are recommended in the absence of contraindications to improve long-term results. In spite of recent developments in cardioplegic cardiac arrest, optimal myocardial protection against perioperative myocardial infarction still remains a challenge.